Application of carrying capacity in reducing the waste produced in tourism area - Mohd Nasir, Nadia; Ibrahim, Mansor (2015)
The lack of waste management strategies in tourism area will lead to undesirable environmental quality. This will gives bad perceptions towards the tourist. Hence, the implementation of carrying capacity concept is an effort to preserve the tourism area as a sustainable tourist destination as well as maintaining its natural value. Based on existing researches, it clearly shows the success of the carrying capacity concept. However, most of it mentioned on the implementation of the concept without stating the exact value of limit for each aspect of tourism.